Inequality in analgesic prescription in Spain: A gender development issue Desigualdad en prescripción de analgésicos en España: Una cuestión de desarrollo de género - Elisa Chilet-Rosell; M. Teresa Ruiz-Cantero; José Fernández Sáez; Carlos Álvarez-Dardet (Elsevier, 2013)
Objectives: It is well known that sex differences in analgesic prescription are not merely the logical result of greater prevalence of pain in women, since this therapeutic variability is related to factors such as educational level or social class. This study aims to analyse the relationship between analgesic prescription and gender development in different regions of Spain. Methods: Cross-sectional study of sex-differences in analgesic prescription according to the gender development of the regions studied. Analgesic prescription, pain and demographic variables were obtained from the Spanish Health Interview Survey in 2006. Gender development was measured with the Gender Development Index (GDI). A logistic regression analysis was conducted to compare analgesic prescription by sex in regions with a GDI above or below the Spanish average. Results: Once adjusted by pain, age and social class, women were more likely to be prescribed analgesics than men, odds ratio (OR) = 1.74 (1.59-1.91), as residents in regions with a lower GDI compared with those in region with a higher GDI: OR Women = 1.26 (1.12-1.42), OR Men = 1.30 (1.13-1.50). Women experiencing pain in regions with a lower GDI were more likely than men to be treated by a general practitioner rather than by a specialist, OR = 1.32 (1.04-1.67), irrespective of age and social class. Conclusions: Gender bias may be one of the pathways by which inequalities in analgesic treatment adversely affect women's health. Moreover, research into the adequacy of analgesic treatment and the possible medicalisation of women should consider contextual factors, such as gender development. Objetivos: Las diferencias por sexo en la prescripción de analgésicos no son simplemente el resultado lógico de una mayor prevalencia del dolor en las mujeres (ya que se relaciona con factores como la educación o la clase social). El objetivo de este estudio fue analizar la relación entre la prescripción de analgésicos y el desarrollo de género de las regiones de España. Métodos: Estudio transversal de las diferencias por sexo en la prescripción de analgésicos en función del desarrollo de género de las regiones. La prescripción de analgésicos, el dolor y las variables demográficas se obtuvieron de la Encuesta Nacional de Salud de 2006. El desarrollo de género se midió con el Índice de Desarrollo al Género (IDG). Se realizó un análisis de regresión logística para comparar la prescripción de analgésicos por sexo en las regiones con IDG mayor o menor que la media española. Resultados: Independientemente del dolor, la edad y la clase social, las mujeres tienen mayor probabilidad de prescripción de analgesia que los hombres, con una odds ratio (OR) = 1,74 (1,59-1,91), así como los residentes de las regiones con menor IDG en comparación con los de regiones con mayor IDG: OR Mujeres = 1,26 (1,12-1,42), OR Hombres = 1,30 (1,13-1,50). Las mujeres que padecen dolor en regiones de menor IDG tienen más probabilidades de ser tratadas por un médico y no por un especialista, con una OR = 1,32 (1,04-1,67). Conclusiones: El sesgo de género puede ser una vía por la cual las desigualdades en el tratamiento analgésico afecta negativamente a la salud de las mujeres. La investigación sobre la conveniencia de la analgesia y la medicalización de las mujeres debería incluir factores de contexto, como el desarrollo de género.